Screening out of wheat varieties against arsenic contaminated soil and irrigation water (Journal of the Asiatic Society of Bangladesh, Science, 2016)
Field trials on wheat were conducted at severely arsenic contaminated areas of Jessore (Chowgacha and Sharsha), Faridpur (Poranpur) and also at low contaminated Shatkhira (Benerpota) during 2010-2011 and 2011-12. The major objective of the study was to screening out of arsenic tolerant wheat varieties. Five varieties of wheat viz. Shatabdi, Bijoy, Prodip, BARI Gom-25 and BARI Gom-26 were tested. Total arsenic contents in the soils were 36.4, 32.8, 28.5 and 6.8 mg kg-1 for Sharsha, Chowgacha, Poranpur and Benerpota, respectively. Irrigation waters contained 0.346, 0.272, 0.238 and 0.140 mg L-1 arsenic for Sharsha, Chowgacha, Poranpur and Benerpota, respectively. No significant variations in yield and yield components among the tested wheat varieties was observed despite of arsenic contaminations in the irrigation water and soil. The variety, Prodip contains 0.043 and 0.028 mg kg-1 arsenic in straw and grain, respectively, which was lower than the other tested varieties. But arsenic contents in all of the tested wheat varieties were found much lower than that of the permissible limit (1 mg kg-1). The transfer coefficient (TC) of arsenic from soil to above ground parts (straw + grain) of wheat varied slightly among the tested varieties where Prodip showed the lowest TC (0.0015-0.0018). However, BARI Gom-24 (Prodip) performed better in terms of arsenic content, uptake, biomass, yield and transfer coefficient and thus can be regarded as arsenic tolerant to a considerable extent.J. Asiat. Soc. Bangladesh, Sci. 42(1): 1-11, June 2016